2019
DOI: 10.5851/kosfa.2019.e29
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sensory Compounds during Dry Aging of Pork Cuts

Abstract: The effects of dry-aging on changes in taste compounds and electronic taste sensing traits of pork were investigated. Ten pork belly and shoulder blade cuts were divided into wet-aging and dry-aging treatments and stored for 21 days at 2°C. The contents of nucleotides and free amino acids, and electronic tongue analysis were investigated at different aging periods (1, 7, 14, and 21 days). The contents of inosine and hypoxanthine of dry-aged pork cuts increased more rapidly, and they were significantly (p<0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Glutamine was the only amino acids that decreased in content throughout the dry ageing in both samples. The observations of the changes in FAAs of dry‐aged pork were similar to previous examinations of dry‐aged beef (Moya et al , ; Koutsidis et al , ; Hwang et al , ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Glutamine was the only amino acids that decreased in content throughout the dry ageing in both samples. The observations of the changes in FAAs of dry‐aged pork were similar to previous examinations of dry‐aged beef (Moya et al , ; Koutsidis et al , ; Hwang et al , ).…”
Section: Resultssupporting
confidence: 89%
“…Studies of the FAAs and metabolites of wet‐ and dry‐aged beef have revealed most of the amino acid contents were increased during the ageing process mainly increased in glutamic acid, tyrosine, leucine, isoleucine and valine (Kim et al , ; Kim et al , ; Dashdorj et al , ). In case of dry‐aged pork, the total amount of FAAs increased 73% over 40 days with dry‐aged pork loin (Lee et al , ), and total amount of FAAs and content of most of FAAs of dry‐aged pork were significantly ( P < 0.05) higher than those of the wet‐aged pork with the abundance of glutamic acid (Hwang et al , ). Glutamic acid imparts the characteristic savoury/beefy (umami) flavour, and tyrosine and leucine confer a bitter flavour; therefore, dry‐aged meat improved taste and palatability (Kim et al , ; Kim et al , ; Dashdorj et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Dry ageing imparts brown-roasted, beefy, buttery, nutty, roasted-nut, and sweet flavor in bovine meat [ 5 , 6 ]. In beef and pig, dry aged meat has an umami taste due to the high level of glutamate [ 7 , 8 ]. In a comparative study on dry aged and vacuum aged meat, it was observed that the umami and butter fried taste were more prominent in dry aged meat.…”
Section: Processingmentioning
confidence: 99%
“…Moreover, the consumer opinion on sensory aspects of dry aged meat was better in comparison to vacuum aged meat, the meat was found to be more tender and juicier. Dry ageing improves the tenderness and juiciness of bovine and porcine meat [ 6 , 7 , 9 ].…”
Section: Processingmentioning
confidence: 99%
“…The preparation of the water-soluble extraction was based on the method of Hwang et al [18]. Minced meat (50 g) was stirred in 200 mL hot distilled water at 95 • C (1:4 w/v) for 10 min before centrifugation at 3000× g for 10 min.…”
Section: Umami Determination By Electronic Tonguementioning
confidence: 99%